Nilai-Nilai Keberagaman dalam QS. al-Hujurat [49]: 13:Kajian Hermeneutika Double Movement Fazlur Rahman - Ana Syelviana; Rezwandi (Al-Misykah: Jurnal Studi Al-qur'an dan Tafsir, 2025)
This study examines the values of diversity contained in QS. al-Hujurat [49]: 13 using Fazlur Rahman's double movement hermeneutic approach. By using the literature review method, this study analyzes how the double movement method can interpret the meaning of verses from their historical context to find universal moral values that can be applied in modern life. The results of the study show that QS. al-Hujurat [49]: 13 contains very important values of diversity, namely: recognizing and respecting human diversity, understanding that diversity is part of Allah SWT's plan, teaching the importance of knowing and understanding differences and emphasizing that a person's nobility is not determined by nation, tribe, or social status, but by piety and devotion to Allah SWT. then the relevance of QS. al-Hujurat [49]: 13 in this modern context is respecting differences, caring and bridging between cultures.